Artificial intelligence and mental health: opportunities and challenges - Stankovska, Gordana; Ahmeti, Aferdita (Przegląd Krytyczny, 2025)
Mental health is a complex field that requires input from multiple disciplines, including psychiatry, psychology, and healthcare. Artificial intelligence researchers need to work closely with mental health professionals to ensure that the implications of artificial intelligence are appropriate and effective for this field. The advancement of artificial intelligence in the 21st century has encompassed various aspects of mental healthcare, including early identification of mental health problems, individualized treatment plans, virtual therapists, advances in teletherapy, and continuous monitoring. Machine learning algorithms can analyse large datasets of patient information, including clinical records, genetic data, and brain imaging scans, to identify patterns and risk factors associated with mental disorders. By integrating this wealth of data, artificial intelligence systems can enhance diagnostic accuracy, assist clinicians in making informed decisions, and potentially enable early detection of mental health conditions. In the context of mental healthcare, where understanding complex human behaviour and emotions is paramount, artificial intelligence offers the potential to revolutionize mental healthcare by providing insights and solutions that were previously beyond the reach of conventional methods. Although artificial intelligence provides opportunities to improve mental healthcare, it also raises ethical considerations about individual freedom, privacy, and the potential for excessive dependence on technology. Integrating artificial intelligence into mental health care would bring many benefits; however, a balanced, complementary approach that emphasizes innovation and human connection can ensure a future in which mental health care is accessible, affordable, compassionate, and effective. Considering the aspects mentioned above, the present study aims to explore the role of artificial intelligence in mental health care, including diagnosis and treatment. Furthermore, we sought to highlight the key challenges, limitations, and opportunities of artificial intelligence in mental healthcare.